The effects of mythomycin C, hylan Gf20 and honey combinations on adhesion formation in laparotomized rats - Saraç, Mehmet; İflazoğlu, Nidal; Ergucuk, Hakan; Gursul, Serdar; Camcı, Cemalettin (My University, 2019)
Aim: Postoperative adhesions are stil unsolved important problems. Some studies have been showed that Mitomycine, Hylan GF-20 and honey can decrease adhesion formation. This study; was planned to aim to compare the adhesion formation effects of Mitomycin C with Hylan GF-20, Mitomycin C with honey and Hylan GF-20 with honey combinations in the laparotomized rats.Material and Methods: Wistar-Albino 70 malerats, weight range between 180-220 gr, divided into 7 groups. After abrasion formation in the rats’ caecum wall and in the peritoneal surface at the localization of right lower quadrant of anterior abdominal wall, Mitomycin C, Hylan GF-20 and honey combinations used and seven days after operation the abdomen was opened for examination.Results: There were statistically significant differences between control group and the study groups according to adhesion formation scala. In all groups that agents were used adhesion formation was decreased, but when the groups comparing the agents used, there was no statistically significant difference.Conclusion: Mitomycin C, Hylan GF-20 and Honey usage in the laparotomized rats decrease adhesion formation. But the combinations of these agents do not show any additional effect to decrease adhesion formation.
Keywords: Tıbbi Araştırmalar Deneysel; Cerrahi